Swamy's pay rules made easy - Muthuswamy; Brinda; Sanjeev (Chennai Swamy publishers, 2023)
This book deals with Pay Rules, Foreign Service and Deputation out of India; Retirement, dismissal, removal and compulsory retirement; Combination of appointments, standard and flat rate licence fee; and Fixation of Pay of Re-employed pensioners.
Keywords: Swamy's; Pay rules made easy